ESTIMATION OF FUNCTIONAL STATE OF CNS USING EEG OF PATIENTS WITH ATRIAL FIBRILLATIONS - Sadullayeva Shamsiyobu Muhiddinovna; Alimova Zulayho Kuvondikovna (TADQIQOTLAR.UZ, 2024)
As is known, atrial fibrillation (atrial fibrillation (AF)) leads to circulatory disorders, changes in the functional state of the central nervous system and, in some cases, to ischemic stroke. At the same time, there is a connection between the duration of heart rhythm disturbances (that is, the constant or paroxysmal form of AF) and the degradation of the higher functions of the central nervous system [1]. In this regard, for patients with MA, it is important to assess the functional state of not only the cardiovascular system, but also the nervous system. At the same time, identifying changes in electroencephalogram (EEG) patterns in heart diseases, as well as in vascular diseases of the brain, is difficult due to the lack of EEG specificity in such patients. The use of functional loads in these cases can help identify the degree of pathological manifestations in the central nervous system and evaluate the restructuring of the electrical activity of the brain in accordance with a frequency equal to or a multiple of the frequency of light pulses. As is known, the severity of such a restructuring is determined by the excitability and lability of cortical neurons, which depends on the ratio of the activating H and deactivating influences of the Co side nonspecific brain systems.